2014
DOI: 10.1007/s11187-014-9572-6
|View full text |Cite
|
Sign up to set email alerts
|

Does health reform affect self-employment? Evidence from Massachusetts

Abstract: This paper evaluates whether the implementation of the 2006 Massachusetts health reform law affected the decision of taxpayers to be selfemployed, using both difference-in-differences and synthetic control methods on a panel of tax returns that spans 1999-2010. Though tenuous, our results suggest that the reform led to a decline in the rate of taxpayers earning a majority of income from self-employment. In addition, it appears to have had a positive impact on earning some self-employment income among joint fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Applying the estimates in DeCicca (), which found a positive impact of nongroup market regulations on self‐employment, one would expect the implementation of the ACA to increase self‐employment in states with lesser levels of pre‐ACA regulation. On the other hand, if the estimates in Heim and Lurie (, ) are valid, one would expect little or no impact on self‐employment. Thus, to test between these two possibilities and to identify the impact of the ACA on self‐employment, we compare changes in self‐employment rates pre‐ and post‐ACA implementation in states that had no such regulations (or had a subset of these regulations) and for which the ACA is a substantial change in policy, to states that had regulations similar to the ACA and for which the ACA is a comparatively minor change in policy.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the estimates in DeCicca (), which found a positive impact of nongroup market regulations on self‐employment, one would expect the implementation of the ACA to increase self‐employment in states with lesser levels of pre‐ACA regulation. On the other hand, if the estimates in Heim and Lurie (, ) are valid, one would expect little or no impact on self‐employment. Thus, to test between these two possibilities and to identify the impact of the ACA on self‐employment, we compare changes in self‐employment rates pre‐ and post‐ACA implementation in states that had no such regulations (or had a subset of these regulations) and for which the ACA is a substantial change in policy, to states that had regulations similar to the ACA and for which the ACA is a comparatively minor change in policy.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…However, Heim and Lurie () examined the passage of these regulations throughout the country, and found no statistically significant effect on the level of self‐employment, though they did find that the composition of the self‐employed changed from younger to older taxpayers. Finally, Heim and Lurie () found that the 2006 Massachusetts health reform law led to a decline in the rate of taxpayers earning a majority of income from self‐employment, though Niu () found no statistically significant long‐run impact of the Massachusetts reform.…”
Section: Related Literaturementioning
confidence: 99%
“…Difference‐in‐difference estimates that use the state‐level introduction of community rating find null effects (Heim and Lurie ), or temporary positive effects (DeCicca ; Heim and Lurie ). Several papers also find mixed effect of the Massachusetts health reform, which established individual and employer mandates, subsidized health insurance for low‐income households, and created a health insurance market place (Heim and Lurie ; Niu 2014).…”
Section: Background and Related Literaturementioning
confidence: 99%
“…Early research has found little impact of the ACA on labor supply (Gooptu et al ; Levy, Buchmueller, and Nikpay ), while previous research on specific reforms finds mixed effects of insurance market reforms on self‐employment (DeCicca ; Heim and Lurie , ; Niu 2014), but positive effects of health insurance tax subsidies (Heim and Lurie ). This research focuses on all workers, but the combination of tax subsidies and market regulations should have the strongest effect on workers with preexisting health conditions.…”
mentioning
confidence: 99%
“…The method consists of creating an artificial counterfactual to estimate the impact of a given intervention on a unit of interest. SCM has gained widespread acceptance in many fields, having been successfully applied in political science (Abadie, Diamond, and Hainmueller 2014;Montalvo 2011), economics (Billmeier and Nannicini 2013;Coffman and Noy 2012;Jinjarak, Noy, and Zheng 2013), education studies (Hinrichs 2012), and public health science (Heim and Lurie 2014). However, SCM has rarely, if ever, been used to evaluate homicide prevention strategies in São Paulo, despite being a useful tool for this particular type of question.…”
Section: Introductionmentioning
confidence: 99%